Profile of Working-Age Patients with Keloid and Hypertrophic Scar at Dr. Soetomo General Hospital Surabaya in 2014-2017 - Fania Ayu Wardani; David Sontani Perdanakusuma; Diah Mira Indramaya (Faculty of Medicine Universitas Airlangga, 2021)
Introduction: Keloid and hypertrophic scar are pathological scars resulting from excessive accumulation of collagen in wound healing process. Data about profiles of keloid and hypertrophic scar are rarely found in Indonesia. Therefore, it is necessary to conduct research related to keloid and hypertrophic scar. This study aimed to provide valuable data for further research.Methods: This was descriptive retrospective study evaluating 105 patients treated for keloid and hypertrophic scar from 2014 to 2017 using medical records of working-age patients.Results: Mostly in patients between 17-25 years old (40%). Comparison between male and female patients were 1.07:1 (keloid) and 1.09:1 (hypertrophic scar). As many as 10.71% of patients of keloid and 17.39% patients of hypertrophic scar were private employees. 23.21% patients with keloid and 23.91% patients of hypertrophic scar were Javanese. 14.29% patients of keloid and 19.57% patients of hypertrophic scar tend to have daily indoor activities. 17.86% patients of keloid and 26.09% patients of hypertrophic scar felt dark-skinned toned. Most keloid scars were caused by traumatic lesions (32.14%), located on the chest (19.54%), and treated by corticosteroid injection. Hypertrophic scar mostly caused by burn injury (54.35%), located on the face (29.55%), and treated by excision surgery.Conclusion: Both keloid and hypertrophic scars were mostly developed in 17-25 years old, male, private employees, Javanese ethnic, dark skin tone patients, with daily indoor activities, caused by traumatic lesion and located on the chest, earlobe, and hand, treated by corticosteroid injection (keloid). Meanwhile, hypertrophic scars are mostly caused by a burn injury on the face and treated by excision surgery.